2013
DOI: 10.1080/07391102.2013.834850
|View full text |Cite
|
Sign up to set email alerts
|

Novel potential inhibitors for adenylylsulfate reductase to control souring of water in oil industries

Abstract: The biogenic production of hydrogen sulfide gas by sulfate-reducing bacteria (SRB) causes serious economic problems for natural gas and oil industry. One of the key enzymes important in this biologic process is adenosine phosphosulfate reductase (APSr). Using virtual screening technique we have discovered 15 compounds that are novel potential APSr inhibitors. Three of them have been selected for molecular docking and microbiological studies which have shown good inhibition of SRB in the produced water from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The RMSD values for hdz-NO 2 in gas (0.431 Å) and water (0.405 Å) phases were lower than the respective values for hdz-CH 3 (0.648 Å in the gas phase and 0.623 Å in water). However, the small RMSD values in all cases showed that the calculated structures correlated pretty well with the respective experimental ones [45,46]. The biggest differences between the theoretical structures and the experimental data corresponded to the aldehyde-derived ring, containing the -CH 3 (or -NO 2 ) substituents, an effect which is more explicit in hdz-NO 2 , probably due to the intrinsic disorder observed in its structure.…”
Section: Tures (Figures S2b and S3b In Supporting Information File 1)...mentioning
confidence: 55%
“…The RMSD values for hdz-NO 2 in gas (0.431 Å) and water (0.405 Å) phases were lower than the respective values for hdz-CH 3 (0.648 Å in the gas phase and 0.623 Å in water). However, the small RMSD values in all cases showed that the calculated structures correlated pretty well with the respective experimental ones [45,46]. The biggest differences between the theoretical structures and the experimental data corresponded to the aldehyde-derived ring, containing the -CH 3 (or -NO 2 ) substituents, an effect which is more explicit in hdz-NO 2 , probably due to the intrinsic disorder observed in its structure.…”
Section: Tures (Figures S2b and S3b In Supporting Information File 1)...mentioning
confidence: 55%
“…There is a dearth of literature using this approach in reducing sulfur production in oil fields. A relatively recent work screened about 15 compounds to find potential inhibitors for Archaeoglobus fulgidus , which though not a bacterium but is also a sulfate-reducing organism. However, the number of compounds screened was quite small and this reduced the possibility of finding an effective compound that will be able inhibit the enzymes responsible for sulfate reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Another remarkable advantage using in silico approach is the opportunity for preparing simulations based on difficult experimental maneuvers. For this reason, simulations emerge as a useful approach to provide insight into the intermolecular complex structure constituted by target and ligand, predicting both mode and free energy bindings by assuming scoring functions [8][9]. In this context, computer experiments were successfully used to investigate protein interactions with aqueous solution elements at different physicochemical conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%